Analisa Kecelakaan Lalu Lintas Pada Jalan Kolektor Kabupaten Aceh Tenggara (Studi Kasus : Jl. Ahmad Yani km, 0 s/d Jl. K. Cane – Medan km, 10) - Taufik, Taufik (Lembaga Riset Ilmiah, 2022)
Abstract - Based on the analysis and discussion that has been described previously, it can be concluded. From the results of the survey and analysis, the capacity of Jalan Kenari and Jalan Manunggal, Southeast Aceh Regency, when it did not experience a reduction in road volume, was 3480.4635 SMP/hour/2 lanes in the morning and the afternoon and evening of 1.4231 smp/hour. Where there is a difference due to differences in the coefficient of the dividing factor, namely in the morning the distribution of vehicle volume is 65% on the route to north-southeast aceh and 35% to west Aceh, while during the day the flow distribution is 50-50. the largest reached 30.19% or 1017.5048 SMP/hour due to the use of one road segment. From the results of the calculation of the degree of saturation (DS) on Jalan Kenari 0.73 for three days and the value (DS) on Jalan Manunggal 0.57. Kenari-Manunggal Market, Southeast Aceh as a place to sell in the morning, there is a significant reduction in road capacity.